(untitled) (Journal of Preventive and Social Medicine, 2022)
Background: To assess the health care facilities provided for senior citizens in selected tertiary hospitals. Methods: This descriptive type of cross-sectional study was carried out among service providers (doctors and nurses) and hospital administrators within the period of January to December 2020. A total of 305 respondents was selected purposively. Semi structured questionnaire and observational checklist was used to collect data. Data was collected by face to face interview and observation. Data was analyzed by using SPSS (Statistical Package for Social Science) software version 25. Results: Among participants, Administrator 2.6%, Doctor 25.2% and Nurse 72.1%. Mean age of the respondents was 32.72±7.67 years. Most of the respondents 90.8% working experience less than 10 years and their average monthly income was Tk. 35398.90±16509.12. In DMCH separate geriatric ward present but in BSMMU geriatric ward absent. Rehabilitation center & long-term care facilities for elderly patients, telemedicine service, separation facility for non COVID geriatric patients from COVID positive patients, free care facility for poor elderly patients, social welfare support facilities present in both hospitals. Separate bed facility in general wards, geriatric ICU and COVID ward absent, training facility on geriatric health absent in both hospitals. Majority of the respondents 97.0% take consent before any procedure, 89.6% service provider involve geriatric patients in decision making about their care and treatment, 56.6% respondents follow polypharmacy guideline. Opinion regarding utility service was average. Opinion regarding diagnostic facilities, essential drugs, sterilization facilities, of this hospital for senior citizens was moderately sufficient 50.5%, 60.6% and 59.3% respectively and ambulance service insufficient 53.4%. Among respondents 89.8% face barriers in providing geriatric health care. Opinion regarding the existing health care facilities for senior citizens of this hospitals insufficient 52.8%. Regarding improvement of health care services 26.0% mentioned that training of doctor/ nurses followed by separate geriatric ward facilities for geriatric patients 20.8%, increase the number of supporting staff 16.2%, free health care facilities for poor elderly patients 11.8%, training of supporting staffs 10.6%, training for informal/family caregiver 7.4%, separate bed for geriatric patient in general wards 6.4% and the rest others mentioned 0.7%. Analysis found statistically significant association between national guideline follow for the treatment and care of older patients and their educational qualification (0.001), designation (p=0.001), polypharmacy guideline follows for the treatment and care of older patients and their designation, referral guideline follows for geriatric patients and their designation (p=0.001). Conclusion: To provide quality healthcare service to the senior citizens of Bangladesh, geriatric health care should be given highest priority. JOPSOM 2021; 40(1): 51-58